90Y radioembolization versus chemoembolization in the treatment of hepatocellular carcinoma: an analysis of comparative effectiveness. (July 2013) - Xing, Minzhi; Kokabi, Nima; Camacho, Juan C; Kooby, David A; El-Rayes, Bassel F; Kim, Hyun S
Locoregional catheter-based therapies for unresectable hepatocellular carcinoma (HCC) include conventional transarterial chemoembolization (cTACE), drug-eluting bead chemoembolization and yttrium-90 ( 90 Y) radioembolization. Although current guidelines recommend cTACE for inoperable HCC, comparative effectiveness of drug-eluting bead chemoembolization and 90 Y radioembolization in the management of HCC remains undefined due to the lack of data evaluating safety and effectiveness among these therapies. A comprehensive search of the literature was carried out for studies examining comparative effectiveness of cTACE and 90 Y based on objective tumor response and overall patient survival. Further data on efficacy, safety, toxicity and cost–effectiveness was also examined. The National Cancer Institute Levels of Evidence for Cancer Treatment Studies provided a useful framework for the critical understanding and stratification of current evidence on locoregional therapy for unresectable HCC. Based on current retrospective cohort studies, evidence for similar efficacy and safety between cTACE and 90 Y radioembolization was demonstrated. Further prospective, randomized studies are required to validate these observations and to analyze cost–effectiveness of these interventions in unresectable HCC patients for definitive recommendations to be made.